Hydrogen-bonding motifs for non-covalent synthesis - Pearson, JM (2013)
This work describes the design and synthesis of a set of four organic molecules that are intended to hydrogen-bond to each other in a pairwise manner. The four hydrogen-bonding units, termed ‘A’, ‘B’, ‘C’ and ‘D’, when placed in solution together, are designed so that A binds only to B, and C binds only to D. Each unit does not bind to itself, nor to either of the other two units to which binding is not intended. For example, A binds to B, but not to A, C, or D. Each unit contains an array of four hydrogen-bonds for strong binding to its partner, is designed to be as rigid as possible, as non-tautomeric as possible, and utilises a staggered non-symmetrical architecture. Of the four intended compounds, three were successfully synthesised (A, B and D). Units B and D were soluble in CDCl3, but Unit A was not. Therefore, the design and synthesis of Unit A was amended, and two variants of Unit A that are both soluble in CDCl3 were successfully synthesised. 1H NMR binding experiments were performed between Unit B and each of the two variants of Unit A. Their binding behaviour was described. A binding constant could not be calculated because the units did not bind in a 1:1 fashion.